Bladder injury by penetration of artificial vessel graft - Wada, Naoki (Hinyokika kiyo. Acta urologica Japonica, 2009)
Iatrogenic bladder injury by artificial vessel graft is extremely rare and only 3 cases have been reported. Herein, we report a case of bladder injury by penetration of artificial vessel graft. An 80-year-old male underwent a femoro-femoral crossover bypass surgery for arteriosclerosis obliterans in our hospital. Postoperatively he complained of urinary incontinence and was referred to the urology department. Ultrasonography for evaluating microscopic hematuria revealed a high echoic linear structure in the bladder and subsequent cystoscopy found an artificial vessel graft penetrating bladder wall. Vascular surgeons reconstructed femoro-femoral bypass and we removed the artificial vessel graft and repaired the injured bladder wall. This is the fourth case of bladder penetrating injury by artificial vessel graft and we summarize the reported cases